Biosorption of Heavy Metal Pollution by Enterobacter agglomerans - Nur Kusuma Dewi; Ibnul Mubarok; Ari Yuniastuti (Biosaintifika: Journal of Biology & Biology Education, 2019)
Biosorption is a new waste treatment technology that can eliminate toxic heavy metals. Biosorption can be considered as an environmentally friendly alternative technology to treat industrial liquid waste that is economically proper to use. One of them is biosorption that utilizes the microorganisms’ absorption ability, especially bacteria that can absorb heavy metals in waters, such as Enterobacter agglomerans. This research aimed to determine the ability of E. agglomerans in reducing heavy metals pollution in local river. The research employed the measurement of the effect of lead (Pb) to E. agglomerans growth using Optical Density (OD) at wavelength 600 nm. The colony numbers were calculated using a standard curve. While the ability of E. agglomerans to reduce heavy metals concentration in liquid media was measured using AAS with a wavelength of 240 nm. The results showed that lead affected the growth of E. agglomerans. The OD value has a negative relationship with the concentration level of Pb. The ODs were decreased from 2.867 to 1.242, using Pb level from 0 ppm to 20 ppm. Therefore, it proved that E. agglomerans could reduce heavy metals concentration in local river in Central Java Province. This research was the first report on E. agglomerans activity on heavy metal in contaminated water. This result can be used as a reference for industrial sites near the river to treat their wastewater before discharging it to the river body to preserve its water purity.